2016
DOI: 10.1080/10824669.2016.1172231
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Strategies to Help the Whole Child: Examining the Contributions of Full-Service Community Schools

Abstract: Full-service community schools are designed to increase students and families' access to comprehensive and coordinated supports, services, and programs such as medical care, food aid, and enrichment activities. Despite widespread support, the research base documenting the efficacy of community schools is still emerging. Analyzing longitudinal data from 6 lowincome, predominantly Latino community schools, this case study investigated whether students' participation in community-school programming influenced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…These academic preparedness differences are strikingly large. Community school literature suggests this variance in college readiness by the school is largely due to meeting students’ holistic educational, health, and social‐emotional needs (Biag & Castrechini, ; Blank, Jacobson, & Pearson, ) through RCCSR programs developed to target the specific needs of displaced and historically marginalized student populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These academic preparedness differences are strikingly large. Community school literature suggests this variance in college readiness by the school is largely due to meeting students’ holistic educational, health, and social‐emotional needs (Biag & Castrechini, ; Blank, Jacobson, & Pearson, ) through RCCSR programs developed to target the specific needs of displaced and historically marginalized student populations.…”
Section: Discussionmentioning
confidence: 99%
“…Provinzano and Sondergeld (in press) also found that the longer students were exposed to integrated supports provided in a community school, the better they did academically, particularly in math. Finally, using longitudinal data from six low‐income community schools, Biag and Castrechini () contend participation in family engagement opportunities and extended learning opportunities can lead to modest gains in attendance and math achievement.…”
Section: Introductionmentioning
confidence: 99%
“…As such, students attending under-resourced schools do not have the same opportunities to thrive academically and socially as their more advantaged peers. Reforming public schools and their surrounding communities continues to be a central strategy for mitigating the effects of poverty on students' well-being and academic performance in school (Biag & Castrechini, 2016). Scholars and practitioners posit that schools offering direct services to address the needs of the whole child have a far greater influence on students' ability to perform well in school (Ladd, 2012) than singular reform initiatives situated in standards and standardization.…”
Section: What Are Community Schools and Why Do We Need Them?mentioning
confidence: 99%
“…Community schools can begin to address opportunity gaps by integrating community members into the classroom, creating learning spaces outside of the classroom, and aligning school and community resources (Biag & Castrechini, 2016; Fehrer & Leos-Urbel, 2016; Sanders, 2018). This can help enrich classroom experiences, making the curriculum relevant to students’ lives and supporting students and communities in areas outside of the school.…”
mentioning
confidence: 99%